The effect of match-play on acute post-match neuromuscular fatigue following Australian Football League Women’s (AFLW) competition - Wilkinson, Emma; Scott, Tannath; Green, Matthew; Hewitt, Adam; Naughton, Mitchell (Biology of Sport, 2025)
The Australian Football League Women’s (AFLW) is the premier national women’s competition in Australian Rules football. The aim of this exploratory study was to investigate the neuromuscular fatigue response to match-play and the external load correlates of this response in AFLW. Players ( n = 22) wore a 10 Hz GNSS device and completed immediately pre- and post-match countermovement jumps (CMJ) on dual force plates for each match in the 2022 AFLW competitive season. Concentric, eccentric, and composite CMJ variables were selected a priori based on previously established validity, reliability, and sensitivity to detect neuromuscular fatigue. The change in each variable from pre- to post-match was analysed using linear mixed effect models and rank bi-serial correlation ( r bs ) effect size statistic. Linear mixed models were also constructed to examine the relationship between external load variables and the change in CMJ metrics. Each player wasincluded as a random effect in these models. Match-play resulted in large negative effects to eccentric mean force, eccentric peak force, and force at zero velocity (all r bs = 0.808 - 0.813), concentric impulse ( r bs = 0.646), flight time:contraction time ( r bs = 0.528), and jump height ( r bs = 0.491). Modelling identified high-speed running distance, repeated highintensity effort bouts, and acceleration load as significant ( p < 0.05) correlates of the change in CMJ variables from pre- to post match. The variance explained in these models was low (Conditional R 2 = 0.128–0.186). Identified CMJ variables may be important to monitor fluctuations in neuromuscular fatigue, whilst external load variables may be useful in examining neuromuscular fatigue correlates in AFLW. Given the exploratory nature of this study, further research is necessary to explore these findings in a hypothesis driven framework.